1989
DOI: 10.3758/bf03210710
|View full text |Cite
|
Sign up to set email alerts
|

Individual gustatory reaction times to various groups of chemicals that provoke basic taste qualities

Abstract: Reaction times (RTs) to four groups of substances that provoke different taste qualities were measured. Measurements for all substances with the same taste, equalized in perceived intensity and provoking a very strong taste, were made concurrently for each subject. The comparisons were made on the individual level. No significant differences in RTs to substances with the same taste quality were found. When the factor of perceived intensity is kept constant, no effect of the stimulus chemical composition on RTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Bujas (1989) showed that the reaction times to 4 groups of taste substances were 373 Ϯ 58.86 ms for salts (NaCl, LiCl), 559 Ϯ 107.61 ms for acids (HCl, citric acid), 602 Ϯ 89.18 ms for sweetness (sucrose, saccharin), and 864 Ϯ 159.60 ms for QHCl, which agreed with our results such that the activity for bitter taste was later than the salty and sweet tastes. He measured the reaction time when the subject stopped the chronometer by manual release of a switch at the moment of taste recogni- tion.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Bujas (1989) showed that the reaction times to 4 groups of taste substances were 373 Ϯ 58.86 ms for salts (NaCl, LiCl), 559 Ϯ 107.61 ms for acids (HCl, citric acid), 602 Ϯ 89.18 ms for sweetness (sucrose, saccharin), and 864 Ϯ 159.60 ms for QHCl, which agreed with our results such that the activity for bitter taste was later than the salty and sweet tastes. He measured the reaction time when the subject stopped the chronometer by manual release of a switch at the moment of taste recogni- tion.…”
Section: Resultssupporting
confidence: 92%
“…The average latency of the time activating the area G using all the data was 327.7 Ϯ 115.5 ms. Kobayakawa and others (1999b) showed in the same measurement system that the average latency of the time of best fit for the earliest ECDs were 155 Ϯ 45.0 ms for NaCl and 267 Ϯ 91.7 ms for saccharin. Bujas (1989) showed that the reaction times to 4 groups of taste substances were 373 Ϯ 58.86 ms for salts (NaCl, LiCl), 559 Ϯ 107.61 ms for acids (HCl, citric acid), 602 Ϯ 89.18 ms for sweetness (sucrose, saccharin), and 864 Ϯ 159.60 ms for QHCl, which agreed with our results such that the activity for bitter taste was later than the salty and sweet tastes. He measured the reaction time when the subject stopped the chronometer by manual release of a switch at the moment of taste recogni- tion.…”
Section: Resultsmentioning
confidence: 99%
“…The negative monophasic potentials that we recorded from the human tongue in response to bitterness of PROP, were characterized by a fast initial depolarization followed by a slow decline, which continued for the entire duration of the stimulation and, in most recordings, even longer. This extended activation could reflect the persistence over time of bitter taste, and its slow increase of intensity, compared to other taste qualities495051. The direct and linear correlation that we found between the amplitude of depolarization evoked by PROP bitter taste stimulation and the density of the fungiform papillae measured in the same area of the tongue where PROP stimulation was delivered, is indicative of the fact that the recorded signals can effectively correspond to the summated response of stimulated taste cells.…”
Section: Discussionmentioning
confidence: 52%
“…Unlike “saltiness” which comes on and fades quickly, “bitterness” seems to grow in intensity and lingers even after the taste trial is over (see [43,44]), characteristics that mirror the time course of our B-best neurons. Human subjects also have longer reaction times for bitter and even sweet stimuli than salts, suggesting different neural latencies [45,46,47]. In rodents, stereotyped oromotor behaviors associated with bitter tastants (i.e.…”
Section: Discussionmentioning
confidence: 99%